2012
DOI: 10.1099/jmm.0.036806-0
|View full text |Cite
|
Sign up to set email alerts
|

Detection of clinically important β-lactamases in commensal Escherichia coli of human and swine origin in western China

Abstract: Data correlating b-lactamases found in commensal Escherichia coli of human and animal origin are limited. In this study, 447 commensal E. coli isolates from the faeces of humans and swine (280 human isolates from four hospitals and 167 swine isolates from seven farms) were collected between September 2006 and January 2009 in western China. For extended-spectrum b-lactamase (ESBL)-producing and other cephalosporin-resistant isolates, the relevant b-lactamase genes (bla TEM , bla SHV , bla CTX-M-1/2/9 group, bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 26 publications
(23 reference statements)
0
31
0
Order By: Relevance
“…In the present study, CTX-M-15, CTX-M-14, and CTX-M-27 enzymes were identified, further highlighting the diversity of the CTX-M groups in pediatric populations. CTX-M-27 enzymes have been reported from farm animals in Asia but are rarely observed in human beings (4,35,36,38). While a diverse mix of CTX-M enzymes was detected in our study, the majority of isolates produced CTX-M-15; thus, the globally prevalent CTX-M-15 enzyme may represent an increasing threat to pediatric populations in the United States as well.…”
Section: Discussionmentioning
confidence: 47%
“…In the present study, CTX-M-15, CTX-M-14, and CTX-M-27 enzymes were identified, further highlighting the diversity of the CTX-M groups in pediatric populations. CTX-M-27 enzymes have been reported from farm animals in Asia but are rarely observed in human beings (4,35,36,38). While a diverse mix of CTX-M enzymes was detected in our study, the majority of isolates produced CTX-M-15; thus, the globally prevalent CTX-M-15 enzyme may represent an increasing threat to pediatric populations in the United States as well.…”
Section: Discussionmentioning
confidence: 47%
“…1 and Supplementary Table S2. Most reports of these alleles have come from Asia, 24,52,58,65,66 with a few isolated accounts from Africa, 23 Europe, 8,34 Australia, 67 South America, 17 Russia, 45 and Canada. 1 Thus, it would appear that this study represents the first report of many CTX-M group 1 alleles in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…A few variants seem to be geographically constrained: (i) bla SHV-106 , only described in Portuguese isolates of K. pneumoniae together with bla TEM-1 , and/or bla CTX- M -32 (Mendonça et al, 2009); (ii) bla SHV-55 , in Portugal (Mendonça et al, 2006; Machado et al, 2007) and recently in Brazil (Dropa et al, 2015); and (iii) bla SHV-57 , in E. coli isolates from Taiwan and China (Ma et al, 2005; Tian et al, 2012). A variant worth to mention is bla SHV-27 (Corkill et al, 2001), that has been detected on different plasmids in E. coli, K. pneumoniae and Enterobacter cloacae , associated with a vast array of antibiotic resistance genes ( bla DHA−1 , bla TEM-1 , bla TEM−1b , bla CMY-2 , bla IMP , bla CTX- M -14 , bla CTX- M -15 , bla SHV-12 , bla SHV-45 , bla OXA-1 , dfrA5, ereA2 ; Muratani et al, 2006; Abbassi et al, 2008; Kiratisin et al, 2008; Duval et al, 2009; Hammami et al, 2011).…”
Section: Origin and Diversity Of The Shv Familymentioning
confidence: 99%